Heterosis In Rice (Oryza Sativa L.) Under Temperate Conditions Of Kashmir (Applied Biological Research, 2011)
Heterosis phenomena was studied for 30 inter-varietal (indica x indica, japonica  x japonica) crosses and 15 inter-subspecific crosses generated through different  mating designs in Kharif 2008 and evaluated for heterosis phenomena for  various morpho-agronomic and other traits under different agro-ecologies of  Kashmir. The basic experimental material comprized of 12 genotypes with six  types belonging to each sub-specific group. For grain yield plant-1 only six inter varietal crosses Jhelum x SK-382, Jhelum x China 1039, SK-382 x SR-1, SR-1 x  Chenab, GS-504 x K-508 and Kohsar x K-508 and no inter-subspecific cross  proved significantly superior over commercial check. For days to 50% flowering,  an important economic character, only cross combinations Koshihikari x GS 508, Koshihikari x K-508 and Kohsar x K-508 flowered earlier as compared to  better parent. The standard heterosis for early flowering was observed on GS 504 x K-508 and Kohsar x K-508. Negative heterosis was observed for grain  yield plant-1 in inter-subspecific crosses, whileas heterosis for all economic  characters was recorded in some inter-varietal crosses. Negative heterosis was  pronounced for most of the cross combinations with respect to most important  economic traits in case of inter-subspecific pool because of high magnitude of  hybrid sterility. There was one to one correspondence between per se performance and heterotic estimates, but such was not the case with SCA effects.  The crosses with high SCA effects viz-a-viz with high standard heterosis can be  exploited to develop early desirable segregants for grain yield and other  morpho-agronomic traits.
Keywords: Heterosis; inter-subspecific crosses; inter-varietal crosses; rice